An evidence mapping study based on systematic reviews of traditional Chinese medicine (TCM) for diabetic retinopathy - Juan Ling; ZhuoLin Xie; XiangXia Luo; Mei Hu; Demián Glujovsky; JiaYuan Zhuang; Yan Wang; Jun Zhou; Deng HongYong (Systematic Reviews)
Abstract Background Diabetic retinopathy (DR) is a leading cause of vision impairment and blindness among individuals with diabetes. Traditional Chinese medicine (TCM) has been explored as an alternative treatment for DR, but the quality of evidence remains uncertain. A comprehensive evidence mapping study is necessary to synthesize existing SRs, identify gaps in the literature, and highlight areas requiring further research. Objective This study aims to evaluate the reporting and methodological quality of SRs on TCM for DR and to assess the effectiveness of TCM interventions using an evidence-mapping approach. Methods A comprehensive search of major biomedical databases to identify relevant SRs published up to November 2023. The reporting quality of the included SRs was assessed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, while the methodological quality was evaluated using the Assessment of Multiple Systematic Reviews 2 (AMSTAR 2) tool. Results A total of 51 SRs involving 131,084 participants were included in the analysis. Evidence mapping indicated that TCM is relatively effective in treating DR. However, the methodological quality and reporting standards of these SRs were generally suboptimal. According to the AMSTAR 2 assessment, only one SR (2%) was rated as high quality, 29 SRs (56.9%) were of moderate quality, 20 SRs (39.2%) were of low quality, and one SR (2%) was of critically low quality. While all studies adequately reported the PICO components, risk of bias assessment, and statistical methods, none provided information on funding sources. Furthermore, only one study (2%) included a list of excluded studies with reasons, and eight SRs (15.7%) documented pre-specified protocols. Common reporting deficiencies included incomplete protocol and registration details, unclear review rationales, and insufficient presentation of relevant outcome data. Conclusion This evidence mapping study highlights the potential benefits of TCM for treating DR while identifying significant gaps in the existing literature. Although TCM interventions show potential benefits for treating DR, the overall quality of SRs is suboptimal. Future research should focus on addressing these gaps, particularly in areas such as funding disclosure and methodological rigor, to enhance the reliability of evidence on TCM interventions for DR.